REGENERASI TOPENG RANDEGAN - Ria Intani (Balai Pelestarian Nilai Budaya Jawa Barat, 2016)
Topeng Randegan is one of the types of art that developed in the village of Randegan, both West and East Randegan, Jatitujuh District, Majalengka Regency. Topeng Randegan in the village of East Randegan is